ANALISIS PENDAYAGUNAAN DANA ZAKAT, INFAQ DAN SHADAQAH DI LEMBAGA AMIL ZAKAT (LAZ) LIDZIKRI KOTA BANDUNG - Erna Nurhasanah (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze the utilization of zakat, infaq, and sadaqah in LAZ Lidzikri Bandung City. The main objective of this research is to understand: how to empower poor communities through the use of zakat funds from LAZ Lidzikri, Bandung City. What are the inhibiting factors in this empowerment, and how are Pakistan's efforts to empower the poor through the use of zakat funds? This research is a qualitative descriptive research with inductive research. Data collection techniques used in this research are observation, interviews, and documentation. Data analysis is done by presenting data, reducing data, and drawing conclusions. The research results show that: LAZ Lidzikri in Bandung City managed to manage zakat, infaq and sadaqah funds effectively for community improvement. The following agenda can be done on economy, perfection, health, LAZ lidzikri has directly supported poor communities by increasing capital uses, including education, and health. Inhibiting factors in the utilization of zakat, infaq and sadaqah funds are that existing programs still have a rigid implementation and lack of innovation.